(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
Weeds are extremely diverse in cultivated land, and their characteristics, habitats, growth, development and distribution are also different. This causes a number of problems for farmers in controlling weeds while growing high grain yields. Especially in the lands where the underground seepage waters are located, when the control measures are not implemented in time, when the rhizomatous weeds, sedges, reeds, sedges, etc. are not implemented, they develop quickly and completely occupy the cultivated area, leading to the complete loss of the possibility of growing agricultural crops in the field.